Anaerobic Contribution Determined in Free-Swimming: Sensitivity to Maturation Stages and Validity - Campos, Eduardo Zapaterra; Kalva-Filho, Carlos Augusto; Silva, Maria Souza; Arruda, Tarine Botta; Gobbi, Ronaldo Bucken; Manchado-Gobatto, Fúlvia Barros; Papoti, Marcelo (Frontiers in Sports and Active Living, 2022)
Evaluation of anaerobic contribution is important under swimming settings (training and modification through ages), therefore, it is expected to change during maturation. The accumulated oxygen deficit (AOD) method can be used to determine the contribution of nonoxidative energy during swimming; however, it requires several days of evaluation. An alternative method to estimate anaerobic contribution evaluation (ACALT), which can also be evaluated without snorkel (i.e., free-swimming, ACFS), has been proposed; however, these methods have never been compared. Thus, this study (i) analyzed the effect of maturation stage on ACFS during maximal 400 m swimming (Part I), and (ii) compared AOD with ACALT and ACFS, determined in a maximal 400 m effort (Part II). In Part I, 34 swimmers were divided into three groups, according to maturation stages (early-pubertal, middle-pubertal, and pubertal), and subjected to a maximal 400 m free-swimming to determine ACFS. In Part II, six swimmers were subjected to one 400 m maximal effort, and four submaximal constant efforts. The AOD was determined by the difference between the estimated demand and accumulated oxygen during the entire effort. The ACALT and ACFS (for Part I as well) was assumed as the sum of lactic and alactic anaerobic contributions. ACFS was higher in pubertal (3.8 ± 1.1 L) than early (2.1 ± 0.9 L) and middle pubertal group (2.4 ± 1.1 L). No difference was observed among absolute AOD (3.2 ± 1.3 L), ACALT (3.2 ± 1.5 L), and ACFS (4.0 ± 0.9 L) (F = 3.6; p = 0.06). Relative AOD (51.8 ± 12.2 mL·kg−1), ACALT (50.5 ± 14.3 mL·kg−1), and ACFS (65.2 ± 8.8 mL·kg−1) presented main effect (F = 4.49; p = 0.04), without posthoc difference. The bias of AOD vs. ACALT was 0.04 L, and AOD vs. ACFS was −0.74 L. The limits of agreement between AOD and ACALT were +0.9 L and −0.8 L, and between AOD and ACFS were +0.7 L and −2.7 L. It can be concluded that ACFS determination is a feasible tool to determine anaerobic contribution in young swimmers, and it changes during maturation stages. Also, ACFS might be useful to measure anaerobic contribution in swimmers, especially because it allows greater speeds.